The Influence of Knowledge Conversion Knowledge Application and Islamic Leadership Style on Employee Performance with Organizational Commitment as an Intervening Variable - Surya Nanda Santika; Alifah Ratnawati (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
This research is intended to identify how the influence of knowledge conversion to work performance, knowledge application to work performnace, Islamic leadership style to work performance and commitment organization on to work performance. Also, to identify how the influence of knowledge conversion, knowledge application, Islamic leadership style to work performance with commitment organization as intervening variable. The population in this study were employee of PT KPJB with included 7 division and employment status permanent and non-permanent. The sample studied in this study were 102 responden who were determined through the Maximum Likelihood (ML) estimation method and purposive sampling. Analysis of research data using SMART – PLS software and partial least square analysus with result of research analysis showing that knowledge conversion is able to influence work performance but not able to influence commitment organization. Knowledge application is able to influence work performance and commitment organization. Islamic leadership style is not able to influence work performance to work performance and commitment organization.